Biomechanics & stroke production: Implications for the tennis coach - Elliott, B. (coachesinfo.com)
Successful tennis performance requires a mix of player talent and player development. This development requires a coach to understand those aspects of sport science pertinent to tennis if a player is to ever reach an optimal level of performance. This introductory article briefly explains the role sport psychology (mental aspects) and exercise physiology (fitness) play in tennis development, before outlining in more detail the role of biomechanics in stroke production. However, the article is primarily aimed at setting the scene for an understanding of the biomechanics of stroke production.